Islamic Social Enterprise at MSMEs in Makassar City: The Relationship Between Islamic Financial Literacy and Social Networks with Product Innovation as Moderating Variables - Helda Rostiani; Amiruddin K; Rika Dwi Ayu Parmitasari (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of Islamic financial literacy and social networks on Islamic social enterprises in MSEs in Makassar City, with product innovation as a moderating variable. The research questions address the extent to which Islamic financial literacy and social networks contribute to improving Islamic social enterprise practices, and whether product innovation can strengthen this relationship. The research method used was a quantitative approach with Structural Equation Modeling (SEM-PLS) analysis techniques. Data were collected through questionnaires distributed to 131 respondents, Sharia MSEs, in Makassar City. Validity and reliability tests, as well as hypothesis testing, were conducted to obtain comprehensive results. The results of the study indicate that Islamic Financial Literacy has a positive and significant effect on Islamic Social Enterprise, while Social Networks have no significant effect. Product Innovation is proven to have a significant direct effect on Islamic Social Enterprise, but does not moderate the relationship between Islamic Financial Literacy and Social Networks on Islamic Social Enterprise. This confirms that Islamic financial literacy is a key factor in strengthening Islamic Social Enterprise, while social networks will only provide benefits if they are built on sharia principles. The implication of this research is the need to improve Islamic financial literacy as the primary foundation for MSEs in building sustainable Islamic Social Enterprises. Social networks need to be strengthened with spiritual values and Islamic collaborative principles to better support social missions. Meanwhile, product innovation should be directed toward Sharia-based social innovations to better align with the goals of Islamic Social Enterprises.